Hero’s Journey Analysis of Denji in The First Part of Chainsaw Man Manga - Aldino Febrian (Passage: Journal of English Language and Literature, 2024)
Manga has become a widely recognized trend around the world, with Western fans tend to prefer psychological and dark fantasy genres in the manga they read (Lin, 2005). One manga that caught the writer’s attention was Tatsuki Fujimoto’s Chainsaw Man., especially the journey of its protagonist, Denji. This research aims to analyze Denji’s journey by utilizing Vogler’s (1992) hero’s journey framework with a qualitative text analysis method. Through analysis of the first part of Chainsaw Man, this research finds typical patterns of Denji’s character development in the context of the hero’s journey. The results of the analysis show that although there are structural differences with the theoretical framework, Denji’s journey in Chainsaw Man reflects universal themes of conflict, character development, and sacrifice. This research contributes to the understanding of manga narrative construction and presents a new perspective on character development in Fujimoto’s work. In conclusion, Chainsaw Man not only enriches the diversity of manga as part of literature works but also becomes a source of ideas for further research on the hero’s journey in manga.